Correlation between skeletal muscle mass index and length of stay in stroke patient - Etisa Adi Murbawani; Hertanto Wahyu Subagio; Dodik Tugasworo Pramukarso; Siti Fatimah Muis; Dwi Pudjonarko; Enny Probosari; Aryu Candra; Martha Ardiaria (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2026)
ABSTRACTBackground: sarcopenia is a syndrome characterized by progressive condition and generalized loss of skeletal muscle mass and strength. It is associated with our prognosis and increased length of stay in stroke patients. Skeletal Muscle Mass Index (SMMI) is an important parameter for assessing skeletal muscle mass and the clinical outcomes of stroke patients.Objective: to investigate the relationship between SMMI and length of stay among stroke patient.Materials and Methods: the cross-sectional observational analytical research was conducted at Dr. Kariadi Semarang Hospital from June 2024 to March 2025 in hospitalized stroke patients aged >18 years. Body composition, including skeletal muscle mass (SMM), is measured using bioelectrical impedance analysis (BIA). Skeletal Muscle Mass will be utilized to calculate the SMMI. Length of stay calculated from admission to discharge from the hospital. Data were analyzed by Independent t-test, Pearson Correlation and Multiple Linear Regression.Results: the average length of stay among the 78 individuals (43 males and 35 females) was 11±3.64 days. The average SMMI levels were normal (7.61± 3.09), indicating no sarcopenia. Skeletal Muscle Mass Index was significantly related with length of stay in stroke patients (r=-0.615; p=0.000) according to the bivariate test.Conclusion: the higher the SMMI values, were correlated with shorter length of stay.Keywords: Length of stay; sarcopenia; skeletal muscle mass index; stroke